Intracellular Thiols and Photo‐Illumination Sequentially Activate Doubly Locked Molecular Probes for Long‐Term Cell Highlighting and Tracking with Precise Spatial Accuracy. Issue 49 (13th October 2014) - Lin, Qiuning; Du, Zengmin; Yang, Yunlong; Fang, Qian; Bao, Chunyan; Yang, Yi; Zhu, Linyong
Abstract A novel photoconvertible fluorescent probe, which can be activated by intracellular thiols, has been synthesized. Such a molecular probe comprises three parts: a 7‐aminocoumarin phototrigger, a thiol‐removable energy acceptor, and a caged fluorescein scaffold with intracellular thiols reactivity as the fluorescent reporter. Extracellularly, the energy acceptor blocks the emission of the coumarin that regulates the photocleavage and photoactivation of the fluorescein. Intracelluarly, the high concentration of thiols releases the energy acceptor, thus activating the S1 state of the phototrigger, which emits coumarin blue fluorescence for pre‐visualization and liberates the caged green‐fluorescent fluorescein to highlight the specific cell upon illumination. Compared to traditional photoactivated organic dyes, the intracellular thiols activated probe requires double activations: one by intracellular thiols and the other by light activation. The dual activations restrict fluorescence precisely inside live cells and at the particular spatial region of light activation, thus a probe with precise spatial accuracy in live cells.